Analysis of Heaving Motion of Purse Seine Vessel Against Regular Waves Following Seas - Ashari, Andi Imran; Paharuddin, Paharuddin (International Journal of Education, Vocational and Social Science, 2023)
The study aims to (1) analyse the technical characters of ship (design, principal dimension, and hydrostatic parameters) and the characteristics of wave (wave length) in connection with heaving motion, and (2) heaving amplitude and encounter frequency that influence the convenience of the ship's crew, its speed and safety. The study was conducted from April to June 2021 at Papandangan Island of Pangkep Regency, South Sulawesi. The data were analysed with numeric analysis, Attwood's formula and Lewis from based on Strip Theory. The study indicates that ships with larger number of characters and ships with a ratio of Lw/Ls = 1.0 (16.75 m, 16.85 m, and 16.95 m) or the wavelength that occurs equals to the length of the ships, the potential of the heaving motion to occur is feeble. Heaving amplitude and encounter frequency with a ratio of Lw/Ls = 1.5 (25.75 m, 25.85 m, and 25.95 m) or the wavelength is larger than the length of the ship. Will influence the convinience of the ship crews, the speed and safety of the ship.